2011
DOI: 10.1371/journal.pone.0029226
|View full text |Cite
|
Sign up to set email alerts
|

Murine and Human Myogenic Cells Identified by Elevated Aldehyde Dehydrogenase Activity: Implications for Muscle Regeneration and Repair

Abstract: BackgroundDespite the initial promise of myoblast transfer therapy to restore dystrophin in Duchenne muscular dystrophy patients, clinical efficacy has been limited, primarily by poor cell survival post-transplantation. Murine muscle derived stem cells (MDSCs) isolated from slowly adhering cells (SACs) via the preplate technique, induce greater muscle regeneration than murine myoblasts, primarily due to improved post-transplantation survival, which is conferred by their increased stress resistance capacity. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 82 publications
3
31
0
1
Order By: Relevance
“…MDSPCs can engraft and stimulate the regeneration of skeletal and cardiac muscles, bone, articular cartilage, and replenish the bone marrow of lethally irradiated mice (37,40,(42)(43)(44)(45)(46). Their high therapeutic value is likely due to their superior survival capability under conditions of oxidative and hypoxic stresses and high expression of antioxidants relative to more differentiated cells, such as myoblasts (47,48). Most recently, our findings showed that i.p.…”
Section: Introductionmentioning
confidence: 65%
“…MDSPCs can engraft and stimulate the regeneration of skeletal and cardiac muscles, bone, articular cartilage, and replenish the bone marrow of lethally irradiated mice (37,40,(42)(43)(44)(45)(46). Their high therapeutic value is likely due to their superior survival capability under conditions of oxidative and hypoxic stresses and high expression of antioxidants relative to more differentiated cells, such as myoblasts (47,48). Most recently, our findings showed that i.p.…”
Section: Introductionmentioning
confidence: 65%
“…In muscle, two populations of satellite cells have been characterized on the basis of their levels of aldehyde dehydrogenase activity. Satellite cells with high levels of activity of this enzyme were shown to be more resistant to cell death in vitro when exposed to H 2 O 2 and in vivo after cell transplantation [92], thus providing a criterion for myogenic progenitors with increased value as therapeutic agents for treating dystrophic muscle [93]. Similarly, high glutathione reductase and superoxide dismutase activity correlated with enhanced regenerative activity of muscle satellite cells [94].…”
Section: Protection From Xenobiotics Genotoxics and Oxidative Stressmentioning
confidence: 99%
“…Recently, we determined that high aldehyde dehydrogenase activity (ALDH high ) is associated with improved cell viability in human myoblasts (Jean et al, 2011). In addition, Vauchez et al and Vella et al have isolated ALDH high muscle progenitors cells that exhibit increased stress resistance and regenerative capacity (Vauchez et al, 2009;Vella et al, 2011). Several ALDH enzymes, including Aldh1a1, Aldh1a2 and Aldh1a3 in humans, catalyze the irreversible oxidation of vitamin A (VA) to retinoic acid (RA), which binds and activates nuclear retinoic acid receptor (RAR)/retinoid X receptor (RXR) heterodimers to regulate the transcription of target genes that are important for development, morphogenesis and differentiation (Jackson et al, 2011;Samarut and Rochette-Egly, 2012).…”
Section: Introductionmentioning
confidence: 99%